Comparative Proteomic Analysis of Plant Acclimation to Six Different Long-Term Environmental Changes. (29th December 2017) - Carrera, Dniel; Oddsson, Sebastian; Grossmann, Jonas; Trachsel, Christian; Streb, Sebastian
Abstract: Plants are constantly challenged in their natural environment by a range of changing conditions. We investigated the acclimation processes and adaptive plant responses to various long-term mild changes and compared them directly within one experimental set-up. Arabidopsis thaliana plants were grown in hydroponic culture for 10 d under controlled abiotic stress (15C, 25C, salt and osmotic) and in nutrient deficiency (nitrate and phosphate). Plant growth was monitored and proteomic experiments were performed. Resource allocation between tissues altered during the plants' response. The growth patterns and induced changes of the proteomes indicated that the underlying mechanisms of the adaptation processes are highly specific to the respective environmental condition. Our results indicated differential regulation of response to salt and osmotic treatment, while the proteins in the changed temperature regime showed an inverse, temperature-sensitive control. There was a high correlation of protein level between the nutrient-deficient treatments, but the enriched pathways varied greatly. The proteomic analysis also revealed new insights into the regulation of proteins specific to the shoot and the root. Our investigation revealed unique strategies of plant acclimation to the different applied treatments on a physiological and proteome level, and these strategies are quite distinct in tissues below and above ground.